Ultrassonografia convencional e Doppler da glândula mamária de caprinos para diagnóstico de mastite - Santos, Victor José Correia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It’s suggested that both B-mode and Doppler ultrasonography could be used to obtain the diagnosis of mastitis in goats on a trustful and non-invasive way, therefore, this study aims to evaluate the sonographic characteristics of the udder and teats and to determine the Doppler indexes of mammary artery at its bifurcation in healthy animals, as well as in animals with both subclinical or clinical mastitis. Thirty animals among Saanen and Alpine Brown goats aged between 2 and 5 years were arranged in three groups, healthy animals (GS), animals with subclinical mastitis (GMSC) and animals with clinical mastitis (GMC). The animals underwent clinical examinations to verify the occurrence of mastitis. The milk was evaluated using the strip cup test and California Mastitis Test (CMT). Using the B-mode, the sonographic characteristics (echotexture and echogenicity) and biometry (diameter and area of the udder cistern, diameter and area of the teat cistern and thickness of the teat wall) were evaluated. Using Doppler ultrasonography, the vascular indexes of the mammary artery were obtained. It was observed hiperecogenicity with solid component in the gland cistern when comparing animals with clinical mastitis and healthy mammary tissue. Regarding the echotexture of the breast tissue, there was heterogeneity in the mammary parenchyma on the three groups, for the milk, it was observed homogeneity for animals on GS and GMSC and heterogeneity for animals on GMC. Grey-scale quantitative assessment revealed increase in echogenicity (mean value) for all the structures when comparing the three groups. Biometry didn’t reveal statistical difference between groups, for none of the evaluated structures. Doppler examination of the mammary artery showed the decrease of final diastolic velocity (VDF) and raise of pulsatility index (IP) between groups. The association of B-mode and Doppler ultrasonography is useful for the evaluation of the udder of ...

Sugere-se que as ultrassonografias convencional e Doppler podem ser utilizadas para se obter o diagnóstico da mastite em caprinos, de forma confiável e não invasiva. Neste trabalho objetivou-se avaliar as características ultrassonográficas das glândulas mamárias e determinar os índices vasculares da artéria mamária de caprinos saudáveis, com mastite subclínica e clínica. Foram utilizadas 30 cabras das raças Saanen e Alpina Francesa em idade reprodutiva (de 2 a 5 anos) divididas em três grupos, animais saudáveis (GS), com mastite subclínica (GMSC) e com mastite clínica (GMC). Os animais foram submetidos ao exame clínico a fim de verificar sinais que indicassem a ocorrência de mastite. O leite foi avaliado pelos métodos da caneca de fundo preto e “California Mastitis Test” (CMT). Por meio da ultrassonografia convencional (Modo-B) do úbere observaram-se as características sonográficas (ecotextura e ecogenicidade) e biométricas das estruturas do órgão (diâmetro e área da cisterna do úbere, diâmetro e área da cisterna da papila mamária, e espessura da parede da papila mamária). Com a ultrassonografia Doppler, foram obtidos os índices vasculares da artéria mamária. Os resultados revelaram hiperecogenicidade com componente sólido para a cisterna da glândula, quando comparado o tecido de animais com mastite clínica com tecido mamário saudável. Em relação à ecotextura do tecido mamário, nos três grupos, verificou-se heterogeneidade do parênquima mamário e para o leite, homogeneidade para animais do GS e GMSC e heterogeneidade para animais do GMC. A avaliação quantitativa da ecogenicidade demonstrou um aumento de ecogenicidade (valor médio) para todas as estruturas ao se comparar os grupos experimentais. A biometria não revelou diferença estatística entre os grupos para nenhuma estrutura avaliada. Ao exame Modo-Doppler da artéria mamária verificou-se redução dos valores obtidos para a ...
Keywords: Caprino; Cabra; Ubere; Glandulas mamarias; Diagnóstico por imagem; Ultrassonografia; Doppler, Ultrassonografia; Udder